Decrement Evoked Potential Mapping: Basis of a Mechanistic Strategy for Ventricular Tachycardia Ablation. (December 2015) - Jackson, Nicholas; Gizurarson, Sigfus; Viswanathan, Karthik; King, Benjamin; Massé, Stephane; Kusha, Marjan; Porta-Sanchez, Andreu; Jacob, John Roshan; Khan, Fakhar; Das, Moloy; Ha, Andrew C.T.; Pashaei, Ali; et al.
Abstract : Background—: Substrate-based mapping for ventricular tachycardia (VT) ablation is hampered by its inability to determine critical sites of the VT circuit. We hypothesized that those potentials, which delay with a decremental extrastimulus (decrement evoked potentials or DEEPs), are more likely to colocalize with the diastolic pathways of VT circuits. Methods and Results—: DEEPs were identified in intraoperative left ventricular maps from 6 patients with ischemic cardiomyopathy (total 9 VTs) and were compared with late potential (LP) and activation maps of the diastolic pathway for each VT. Mathematical modeling was also used to further validate and elucidate the mechanisms of DEEP mapping. All patients demonstrated regions of DEEPs and LPs. The mean endocardial surface area of these potentials was 18±4% and 21±6%, respectively ( P =0.13). The mean sensitivity for identifying the diastolic pathway in VT was 50±23% for DEEPs and 36±32% for LPs ( P =0.31). The mean specificity was 43±23% versus 20±8% for DEEP and LP mapping, respectively ( P =0.031). The electrograms that displayed the greatest decrement in each case had a sensitivity and specificity for the VT isthmus of 29±10% and 95±1%, respectively. Mathematical modeling studies recapitulated DEEPs at the VT isthmus and demonstrated their role in VT initiation with a critical degree of decrement. Conclusions—: In this preliminary study, DEEP mapping was more specific than LP mapping for identifying the critical targets of VT ablation. The mechanism of DEEPs relates to conduction velocity restitution magnified by zigzag conduction within scar channels.